Causal effects of financial education intervention aimed at University students on financial knowledge and financial self-efficacy - Manuel Salas-Velasco (Journal of Risk and Financial Management, 2022)
Based on a randomized controlled experiment among final-year undergraduate students, we provide an assessment of the treatment effects of financial education intervention focused on debt-financed graduate education decision-making. Specifically, this study finds positive treatment effects on both college seniors' objective financial knowledge and subjective financial knowledge and self-confidence (i.e., perceived financial self-efficacy). Individual financial well-being is thought to be enhanced by improved financial knowledge test scores and perceived financial self-efficacy. In addition, we carry out a causal mediation analysis to investigate the extent to which objective financial knowledge plays a mediating role in the effect of financial education treatment on the intervention outcome (perceived financial self-efficacy). The mediation proportion, the proportion of treatment effect on outcome explained by the intermediate variable of financial knowledge, is around 21%, which is important. Thus, policies that aim to improve financial capabilities among college students through financial education programs should be aware that financial literacy is a significant antecedent of (a prerequisite for) financial self-efficacy.
Keywords: 650; causal mediation analysis; financial education; financial literacy; financial self-efficacy; randomized controlled experiment